PENINGKATAN HASIL BELAJAR TEMA 1 MUATAN IPA MELALUI METODE FISHBOWL PADA SISWA KELAS V SDN 09 TALAWI HILIR - Sutisnawati Sutisnawati (STKIP Pesisir Selatan, 2019)
Based on student learning outcomes VSDN 09 Talawi Hilir class in subject matter of sub-science explained the motion equipment and its function in animals and humans as well as how to maintain the health of human locomotor was found that the learning outcomes of Theme 2 of the science content is still very low. The average student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about the improvement of learning outcomes Theme 1 The contents of the Natural Sciences sub explained the motion equipment and its functions in animals and humans as well as how to maintain the health of human motion equipment through the Fishbowl Method in Class VSDN 09 Talawi Hilir Sawahlunto City. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 19 students of Class V SDN 09 Talawi Hilir. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that has been presented, it can be concluded that the Fishbowl Method can improve learning outcomes Theme 2 of the IPA content sub explains the locomotor and its functions in animals and humans and how to maintain the health of human locomotor in SDN 09 Talawi Hilir. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 55.13 (enough) increased to 84.22 (good) with an increase of 29.09%.